Hungarian Folk Music - Bartók, Béla 1881-1945; Calvocoressi, Michel-Dimitri (London Oxford University Press, 1931)
Bela Bartok, one of the outstanding composers of the twentieth century, was born in Hungary in 1881. Between 1899 and 1903, he attended the Academy of Music in Budapest; in 1907 he was appointed professor of piano. Bartok's early compositions were complex and not well received by the public. In 1905 he turned his attention to collecting and cataloging the folk music of his native Hungary. With the help of his friend and fellow Hungarian, composer Zoltan Kodaly, Bartok produced a series of commentaries, anthologies, and arrangements of the folk music that he had collected. Bartok's interest in folk music had a profound effect on his compositions. The influence is seen in the unadorned power of his music, especially in the rhythmic drive of fast movements and in his use of folk melodies, rhythms, and harmonic patterns.
Keywords: 20th Century (1901-2000); Music history; Folk music; Song; Hungary